Back cover: Identification of pinostilbene as a major colonic metabolite of pterostilbene and its inhibitory effects on colon cancer cells. Issue 9 (September 2016) - Sun, Yue; Wu, Xian; Cai, Xiaokun; Song, Mingyue; Zheng, Jinkai; Pan, Che; Qiu, Peiju; Zhang, Lijuan; Zhou, Shuangde; Tang, Zhonghai; Xiao, Hang
Abstract : Mol. Nutr. Food Res . 2016, 60, 1924–1932. DOI:10.1002/mnfr.201500989 Dietary pterostilbene, a resveratrol derivative found in blueberries, is transformed to pinostilbene via demethylation in mice. The level of pinostilbene in the colonic mucosa of pterostilbene‐fed mice is relatively high, and at that level, pinostilbene inhibits human colon cancer cell growth by inducing cell cycle arrest and apoptosis.